Predictive factors of ketoacidosis in type 1 diabetes mellitus - Listianingrum Listianingrum; Suryono Yudha Patria; Tunjung Wibowo (Indonesian Pediatric Society, 2019)
Background Diabetic ketoacidosis (DKA) is an acute complication in type 1 diabetes mellitus (DM) and a significant cause of morbidity and mortality in developing countries. Diabetic ketoacidosis can be prevented by good management of the disease. Risk factors from previous studies that increase the DKA incidence were peripubertal age, female gender, low socio-economic status, low parental education status, DKA at the first diagnosis of type 1 DM, infection, psychological problems, poor metabolic control, and non-compliance with insulin treatment. Objective To determine whether sex, age, socio-economic status, parental education level, DKA at the initial diagnosis of type 1 DM, infection, psychological problems, poor metabolic control, and failing to take insulin as needed were predictive of DKA in type 1 DM patients. Methods We conducted a retrospective cohort study using medical records from type 1 DM patients aged 0-20 years, at the Department of Child Health, Dr. Sardjito Hospital, Yogyakarta, from January 2011 to May 2017. We assessed for the incidence and predictors of DKA. Logistic regression analysis was done to determine which factors increased DKA incidence. Results A total of 57 type 1 DM patients were recruited, with DKA incidence of 37 (65%). Five (8.8%) DKA patients died. Multivariate analysis revealed that infection (OR 5.23; 95%CI 1.47 to 19.68; P=0.014) and DKA at the first diagnosis of type 1 DM (OR 5.37; 95%CI 1.40 to 19.52; P=0.011) were significant risk factors for DKA. Conclusion Infection and DKA at the first diagnosis of type 1 DM are significant predictors of increased DKA incidence.